2022
DOI: 10.1111/1462-2920.15898
|View full text |Cite
|
Sign up to set email alerts
|

Clostridioides difficile infection and One Health: an equine perspective

Abstract: Clostridioides (Clostridium) difficile presents a significant health risk to humans and animals. The complexity of the bacterial-host interaction affecting pathogenesis and disease development creates an ongoing challenge for epidemiological studies, control strategies and prevention planning. The recent emergence of human disease caused by strains of C. difficile found in animals adds to mounting evidence that C. difficile infection (CDI) may be a zoonosis. In equine populations, C. difficile is a known cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 127 publications
0
7
0
Order By: Relevance
“…In general, although the pathological lesions observed in animals with CDI are similar to those described in humans [9], clinical manifestations can vary among the different animal species [4,16]. Among food-producing animals, CDI prevalence has been reported globally in both swine (mean value 43%, range 0-100%) and cattle (mean value 14%, range 0.5-56.4%) [19]. In particular, CDI prevalence and mortality is very high in neonatal piglets with rates that can reach up to 100% and 50%, respectively [4,16,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 74%
“…In general, although the pathological lesions observed in animals with CDI are similar to those described in humans [9], clinical manifestations can vary among the different animal species [4,16]. Among food-producing animals, CDI prevalence has been reported globally in both swine (mean value 43%, range 0-100%) and cattle (mean value 14%, range 0.5-56.4%) [19]. In particular, CDI prevalence and mortality is very high in neonatal piglets with rates that can reach up to 100% and 50%, respectively [4,16,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 74%
“…In horses, there have been inconsistencies in the reported prevalence and perceived impact of C. difficile , with prevalence ranging from 5% to 90%, although it seems to be higher in foals. At a molecular level, strains not associated with other species as well as those identified in other animals, the environment, and humans have been isolated [ 9 ].…”
Section: Molecular Epidemiology Of C Difficilementioning
confidence: 99%
“…Several studies have identified C. difficile in a great variety of animal species, including livestock, pets, and wildlife [ 9 , 10 , 11 , 12 , 13 , 14 ]. This fact has raised concerns about potential zoonotic transmission, where animals may serve as reservoirs and a source of infection for humans through direct contact or consumption of contaminated animal products.…”
Section: Introductionmentioning
confidence: 99%
“…C. difficile has been isolated from the gut of most mammals [20] including cattle, horses, pigs, and poultry [21][22][23][24][25][26][27] as well as companion animals such as dogs and cats [28][29][30]. Studies have also demonstrated the prevalence of C. difficile in the environment, including sand playgrounds [31], public gardens [32], rivers [33], soil [17,34,35], water [36], and environments in contact with farm animals [23].…”
Section: Introductionmentioning
confidence: 99%
“… C. difficile has been isolated from the gut of most mammals [20] including cattle, horses, pigs, and poultry [21–27] as well as companion animals such as dogs and cats [28–30]. Studies have also demonstrated the prevalence of C.…”
Section: Introductionmentioning
confidence: 99%